KONSTRUKSI DAN TRANSFORMASI NILAI KETUHANAN YANG MAHA ESA DALAM PENDIDIKAN KEWARGANEGARAAN DI PERGURUAN TINGGI (Studi Kasus Pengembangan Pendidikan Kewarganegaraan Sebagai Pendidikan Anti Korupsi Pada Universitas Pasundan) - Subelo Wiyono, - (2021)
ABSTRACT The current study examined the value construction and transformation of Ketuhanan yang Maha Esa in Civic Education. The application of Pancasila values, which is based on spiritualism, personalizes an anti-corruption character. Various criminal acts of corruption have caused serious issues in a lot of areas; economy, society, governance, politics and democracy, law enforcement, defense and security, and several important aspects. The examination of the study involves the ontology and epistemology of Pancasila within Civic Education as a foundation of students' akhlakul karimah (moral values) through local wisdom as a means of preventive action. The study adopted a case study design within a qualitative approach in an attempt to seek possibilities drawn in this study. The study was conducted in one of the private universities in Bandung, namely UNPAS, after giving some thoughts on some research considerations that it holds a vision to develop the Islamic values reflected in Pengkuh Agamana and Jembar Budayana '. Therefore, the belief is in line with the aim of this study, which is to revive the moral value of Ketuhanan yang Maha Esa. The data collection process includes observation and interviews with lecturers of Civic Education, experts in related fields (philosophy of Pancasila, Civic Education, and law), relevant literature, and also students. The conclusion of the examination is: (1) anti-corruption education is an essential undertaking, yet this essential action is not fully supported by a curriculum that runs specific issues about the anti-corruption character. The absence of anticorruption learning methods becomes an obstacle in determining the very foundation of the establishment of anticorruption character, which makes possible the birth of various teaching methods initiated by the lecturers in constructing the anticorruption character among students. (2) Anti-corruption education lacks a specific theoretical approach regarding the moral values of an anticorruption character. Such values should have become the ground point of the character-building process. (3) Civic education could be developed as a medium to encourage a character maturing process based on spiritualism. (4) The anticorruption formation through spiritual values (Ketuhanan) method could be utilized in developing students' character. As a nation which highly praises the spiritual values, students should apply these values in their social life - not only individually, but also collectively as a community. (5) In general, Pancasila and Civic Education as subjects have already possessed the basic foundation to establish the anticorruption character. (6) Sundanese culture as a pearl of local wisdom has anticorruption values. Keywords: Civic Education, Pancasila, spiritual values, anticorruption character